2022
DOI: 10.24310/espsiescpsi.v15i1.13673
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias cognitivas para afrontar situaciones de acoso/ciberacoso: diferencias entre chicos y chicas

Abstract: La violencia entre iguales provoca un impacto negativo sobre la salud de los adolescentes implicados. Entre los factores que han mostrado evidencias para predecir la realización y el sufrimiento de conductas agresivas, se encuentran las estrategias de afrontamiento cognitivo-emocional. Sin embargo, en contextos de acoso y ciberacoso pocos estudios han analizado el papel de estas estrategias y, aún menos, de manera separada para chicos y chicas. Por ello, este estudio planteó dos objetivos: analizar las diferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…From the present research, it was found that students with a lack of social skills and who use cognitive avoidance as a coping strategy are more likely to suffer from anxiety. It is thus demonstrated that dysfunctional or maladaptive strategies produce or are associated with higher levels of anxiety, which is in line with other authors [54]. summary, school anxiety is a considerable challenge faced by many students, but with appropriate interventions focused on coping strategies and social skills, students can be offered essential tools to manage and reduce their anxiety levels.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From the present research, it was found that students with a lack of social skills and who use cognitive avoidance as a coping strategy are more likely to suffer from anxiety. It is thus demonstrated that dysfunctional or maladaptive strategies produce or are associated with higher levels of anxiety, which is in line with other authors [54]. summary, school anxiety is a considerable challenge faced by many students, but with appropriate interventions focused on coping strategies and social skills, students can be offered essential tools to manage and reduce their anxiety levels.…”
Section: Discussionsupporting
confidence: 86%
“…It has been observed that the use of adaptive coping strategies, such as problem-solving or cognitive reappraisal, can help reduce school anxiety [52,53]. In contrast, maladaptive coping strategies, such as avoidance or rumination, may increase school anxiety [54][55][56].…”
Section: Introductionmentioning
confidence: 99%